Pelanggaran Etika Pariwara Indonesia pada Iklan Komersial K Natural White dan Buavita di Global TV - Afiannur, Restu Rizqy; Musa, Ivan Wisnu; Firmansyah, Riffat; Junaedi, Fajar (Universitas Muhammdiyah Yogyakarta, 2025)
This study aims to analyze violations of the Indonesian Advertising Ethics (EPI) in the advertisements of K Natural White and Buavita products broadcast on television. This research employs a descriptive qualitative method using observation and documentation approaches to identify and analyze advertising content that breaches ethical principles. The findings reveal that the K Natural White advertisement violates the EPI clause on honesty due to claims such as